The agency of mathematics clubs as panacea for efficacious pedagogical praxis: A grade 3 case study - Hebe, Headman; Hebe, Gasenakeletso (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Mathematics is, universally, considered the heartbeat of the Science, Technology, Engineering and Mathematical (STEM) education. Accordingly, the learners must be equipped with strong mathematical proficiency very early in life. This behoves mathematics practitioners to use various impactful pedagogical strategies. The bigger action research from which this paper derives investigated, through the use of qualitative and quantitative approaches, the potential of mathematics clubs as a strategy to improve learner performance in early childhood education (ECE). Since there is already a published report on the bigger study, this paper focuses only on teasing out the factors that enabled the success of the maths clubs which participated in this study. The current study is essential because the literature reviewed underscores a paucity of research that focuses on factors enabling the efficacy of maths clubs. This qualitative study relied on interviews with participant-teachers and observations by the field researcher. Vygotsky’s sociocultural framework and the Appreciative Inquiry model underpinned and guided the study. The findings of this study indicate the following as efficacy-enablers in maths clubs: play-based pedagogy, code-switching, the use of real-life scenarios in pedagogy, learner independence in problem-solving, participant collaboration and small classroom sizes. The study advocates for more research on factors enabling effectiveness in maths clubs and challenges policy decision-makers to transform everyday classroom settings to model mathematics clubs scenarios.